2021
DOI: 10.3390/life11121382
|View full text |Cite
|
Sign up to set email alerts
|

Long Non-Coding RNA PVT1 and Its Target miRNA-146a as Potential Prognostic Biomarkers in Rheumatoid Arthritis Patients

Abstract: Objective: Long non-coding RNAs (lncRNAs) and their target microRNAs were documented in multiple studies to have a significant role in different joint disorders such as rheumatoid arthritis (RA) and osteoarthritis (OA). The current work aimed to determine the potential role of lnc-PVT1 and miR-146a as promising biomarkers to distinguish between RA, OA patients, and healthy individuals. Methods: The expression levels of lnc-PVT1 and its target miR-146a in the serum were measured for three different groups, incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 59 publications
1
5
0
Order By: Relevance
“…In this study, when compared with controls, we discovered that the expressions of miRNA 146a and miRNA 155 were significantly higher in the serum of RA patients. This finding was in agreement with numerous research that estimate the expression of both miRNAs in synovial fluid, PBMC, synovium, synovioblast and specific cells in RA patients [19][20][21][22][23][24] . Filková and colleagues 25 discovered decreased levels of miR-146a and miR-155 in the sera of individuals with early RA compared to those with chronic RA.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In this study, when compared with controls, we discovered that the expressions of miRNA 146a and miRNA 155 were significantly higher in the serum of RA patients. This finding was in agreement with numerous research that estimate the expression of both miRNAs in synovial fluid, PBMC, synovium, synovioblast and specific cells in RA patients [19][20][21][22][23][24] . Filková and colleagues 25 discovered decreased levels of miR-146a and miR-155 in the sera of individuals with early RA compared to those with chronic RA.…”
Section: Discussionsupporting
confidence: 92%
“…Our research revealed that the best cutoff of miRNA 146a in prediction of RA is ≥2.694 with area under curve 0.857, sensitivity 77.4% and specificity 80.6% (P<0.001). In support of this finding, Erfan et al 21 demonstrated that miRNA-146a can be accurate in the diagnosis of RA with an AUC of 0.836 at a cut-off value of ≥1.433 folds with a sensitivity and specificity of 82.5% and 100%, respectively. Consequently, it is able to differentiate between healthy controls and patients with early RA.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…The disorder of microRNA profile acts as a biomarker event for RA progression [ 6 ]. Moreover, accumulating reports have indicated that miRNAs directly regulate RA development via influencing the proliferation, inflammatory level, and cellular molecular signal transduction of RA-FLSs [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…LINK-A regulates RA FLS invasion and inflammation through HIF-1α and/or miR-1262 pathways, which might be a promising therapeutic target for RA ( 152 ). lncRNA growth arrest-specific transcript 5 (GAS5) is significantly downregulated in synovial tissues, serum, and PBMCs of RA patients compared with HCs and negatively correlated with IL6, IL-17, CRP, ESR, DAS28, and anti-CCP, suggesting that it could be used as a potential biomarker for RA diagnosis ( 153 156 ). Interestingly, lncRNAs GAS5 (3.31-fold), RNA component of mitochondrial RNA-processing endoribonuclease (RMRP) (2.43-fold), and TNF-α and heterogeneous nuclear ribonucleoprotein L (THRIL) (2.14-fold) were significantly upregulated in the circulating T cells of RA patients compared with controls, and the ROC curve analysis of the three indicated their value in discriminating RA patients from controls ( 157 ).…”
Section: Candidate Rnas As Biomarkers For Ramentioning
confidence: 99%